1984
DOI: 10.1073/pnas.81.15.4960
|View full text |Cite
|
Sign up to set email alerts
|

Monensin-induced inhibition of cell spreading in normal and dystrophic human fibroblasts.

Abstract: Cultured skin fibroblasts from normal individuals and from patients with Duchenne muscular dystrophy spread equally rapidly when seeded on a glass substratum. Exposure to the ionophore monensin substantially suppresses normal and dystrophic fibroblast spreading in serum-free media for up to at least 100 min. Preincubation of normal fibroblasts with monensin causes a further reduction in cell spreading. Dystrophic fibroblasts fail to spread as well as normal cells after monensin preincubation. Such findings ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 40 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…We suggest that this may be a consequence of the known effects (68) of monensin on inhibiting the translocation of nascent glycoproteins which may be involved in recognition and adhesion at the cell surface. We have previously shown that only 30 min exposure to 0.5 IxM monensin is sufficient to reduce cell-substratum adhesive interactions in human skin fibroblasts (52,53).…”
Section: Discussionmentioning
confidence: 99%
“…We suggest that this may be a consequence of the known effects (68) of monensin on inhibiting the translocation of nascent glycoproteins which may be involved in recognition and adhesion at the cell surface. We have previously shown that only 30 min exposure to 0.5 IxM monensin is sufficient to reduce cell-substratum adhesive interactions in human skin fibroblasts (52,53).…”
Section: Discussionmentioning
confidence: 99%
“…DMD skin fibroblast populations in vitro express a variety of syndrome-specific cellbiological (6)(7)(8)(9)(10), and biochemical (11)(12)(13)(14)(15)(16)(17) abnormalities. Recent investigations into the protein turnover in DMD fibroblasts in vitro (18)(19)(20) (17) and from our laboratory (20) indicate a significant decrease in protein synthesis (17,20) and a significant increase in the degradation of short-and long-lived proteins in DMD fibroblast populations in vitro (20).…”
mentioning
confidence: 99%